Helping business english learners improve discussion skills - Uribe Enciso, Olga Lucia (Colombian Applied Linguistics Journal, 2012)
Developing discussion skills is a central task in Business English (BE), as doing business involves negotiating meaning and persuasive power in order to realize one’s transactional intentions. A group of BE learners in Colombia did not recognize L2 verbal and non-verbal turnyielding conventions, nor did they know how to interrupt or to deal with interruptions successfully. Additionally, they did not know how to deal with backchannels. Consequently, some classroom activities were aimed at helping learners notice how spoken communication devices work in different cultures, using mechanisms to signpost their turn and deal with unexpected interruptions, and becoming familiar with backchannels. After eight three-hour lessons learners became more sensitive to spoken discourse elements and expanded their gambits and backchannels repertoire.